Logistics Outsourcing: A Review of Basic Concepts - LATIFA FADILE; Mohamed El Oumami; Zitouni Beidouri (International Journal of Supply Chain Management, 2018)
The proliferation of new information technologies, intense business competition, transactions acceleration, rapid product obsolescence, shorter product life cycle and changing customer needs and requirements, have pushed firms to reorganize, to revise their businesses strategies and to refocus on their core businesses. In response to these challenges, many firms start to outsource more of their business functions including the logistics ones. Logistics outsourcing has become a common practice by many firms, whether they are local or multinational, small or large. And it has attracted attention of both researchers and practitioners. The aim of this paper is to provide a general overview of logistics outsourcing through presenting the state of the art research in this field, exhibiting the different related concepts and based on that, suggesting future research directions.